Reforming Stop-and-Frisk - Fradella, Henry F. (Criminology, criminal justice, law & society, 2017)
Although stop-and-frisk has a long history as a policing tactic rooted in particularized, reasonable suspicion of criminal activity, several U.S. jurisdictions morphed stop-and-frisk into a broad and sometimes aggressive crimecontrolstrategy. The recent experiences in many jurisdictions demonstrate a strong disconnect between constitutionally sanctioned principles and policing practice. Arguably, stop-and-frisk has become the next iteration of a persistent undercurrent in racial injustice in American policing. Although stop-and-frisk has a legitimate place in 21st-century policing, changes must be made to prevent officers from engaging in racially biased or otherwise improper and illegal behavior during stops of citizens. Recommended reforms include better selection of police personnel during recruitment, improved training, clearer administrative policies, enhanced supervision of officerswith corresponding accountability mechanisms, and external oversight.